2000
DOI: 10.1080/026783700417212
|View full text |Cite
|
Sign up to set email alerts
|

A test of the Maslach Burnout Inventory in three samples of healthcare professionals

Abstract: Structural equation modelling with LISREL was used to investigate the factor structure of the Maslach Burnout Inventory (MBI). Emotional exhaustion was the most robust of the MBI's three factors, followed by depersonalization, while the personal accomplishment factor performed weakly. A new measurement model was developed in a sample of 197 nurses consisting of the emotional exhaustion and depersonalization dimensions, which were measured with ve and two empirical MBI indicators, respectively. A test of invari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
147
0
14

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(168 citation statements)
references
References 43 publications
7
147
0
14
Order By: Relevance
“…This process could result with creating a new instrument for analyzing the level of professional burnout in substance abuse counsellors. Even though former studies on professional stress confirmed three factorial structure of MBI [1,[32][33][34][35], our conclusion is in agreement with a number of other reliability and validity studies of MBI [36][37][38][39]. Some studies even recommended two factorial structures: first factor was defined by the EE and DP items and was named "the core of Burnout", and the second factor was defined by the PA-items [37], which is in accordance with our results.…”
Section: Discussionsupporting
confidence: 92%
“…This process could result with creating a new instrument for analyzing the level of professional burnout in substance abuse counsellors. Even though former studies on professional stress confirmed three factorial structure of MBI [1,[32][33][34][35], our conclusion is in agreement with a number of other reliability and validity studies of MBI [36][37][38][39]. Some studies even recommended two factorial structures: first factor was defined by the EE and DP items and was named "the core of Burnout", and the second factor was defined by the PA-items [37], which is in accordance with our results.…”
Section: Discussionsupporting
confidence: 92%
“…In the past month, 60.4% of subjects had thoughts of leaving their work. Table 2 shows the scores for emotional exhaustion (EE), depersonalization (DP) and personal accomplishment (PA), which were lower than those for the overall sample of the MBI-HSS subscales 6,19) (n=1,106, mean (SD): 20.99 (10.75) for EE, 8.73 (5.89) for DP, 34.58 (7.11) for PA) from the original instrument designed for service providers in the human services field. The overall sample utilized to norm the measure (n=11,067) included individuals from the following subgroups: elementary and secondary education, postsecondary education, social services, medicine and mental health 6,23) .…”
Section: Demographic Characteristics and Turnover Intentionmentioning
confidence: 92%
“…The Chinese version of Maslach Burnout Inventory (MBI) 19) includes 22 items on a 7-point Likert scale (0, never; 1, a few times a year or less; 2, once a month or less; 3, a few times a month; 4, once a week; 5, a few times a week; 6, every day). The items are grouped in three dimensions: (a) emotional exhaustion (EE), (b) depersonalization (DP) and (c) personal accomplishment (PA).…”
Section: Burnoutmentioning
confidence: 99%
“…5 The completion of an electronic questionnaire was performed on a voluntary and private basis, thereby minimising response bias. In addition, it was conducted through a third party, which ensured respondent confidentiality.…”
Section: Research Design Data Collection Methods and Research Instrumentioning
confidence: 99%